Butterfly boy : memories of a Chicano mariposa - González, Rigoberto (Madison : University of Wisconsin Press, 2006)
"Heartbreaking, poetic, and intensely personal, this is a unique coming-out and coming-of-age story of a first-generation Chicano who trades one life for another, only to discover that history and memory are not exchangeable or forgettable. Growing up among poor migrant Mexican farmworkers, González also faces the pressure of coming-of-age as a gay man in a culture that prizes machismo. Losing his mother when he is twelve, González must then confront his father's abandonment and an abiding sense of cultural estrangement. His only sense of connection gets forged in a violent relationship with an older man. By finding his calling as a writer, and by revisiting the relationship with his father during a trip to Mexico, González finally claims his identity at the intersection of race, class, and sexuality. The result is a leap of faith that every reader who ever felt like an outsider will immediately recognize"--From publisher description.
pt. 1. Smarting points, starting points -- Summer's passage, Southern California, 1990 -- Welcome to Indio, California, Pop. 36,793 -- Ghost whisper to my lover -- Now leaving Mexicali, Baja California, Norte -- Ghost whisper to my lover -- pt. 2. Childhood and other language lessons -- Bakersfield, California, 1970-72 -- Zacapu, México, 1972-79 -- Thermal, California, 1979-80 -- Thermal, 1981-82 (Our little home on top of the garage) -- Summer's passage -- pt. 3. Adolescent mariposa -- Ghost whisper to my lover -- Indio, 1983-88 ("El Campo" years) -- pt. 4. Zacapu days and nights of the dead -- Summer's passage -- Ghost whisper to my lover -- Zacapu, July 1990 (Imago) -- pt. 5. Unpinned -- Riverside, California -- Ghost whisper to my lover.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: González, Rigoberto; González, Rigoberto; Authors, American -- 20th century -- Biography; Hispanic American gay people -- Biography; Gay men -- Biography; Gay men -- Biography; Écrivains américains -- 20e siècle -- Biographies; Personnes homosexuelles américaines d'origine latino-américaine -- Biographies; Homosexuels masculins -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; LITERARY CRITICISM -- American -- General; Authors, American; Gay men; Hispanic American gays; 1900-1999; autobiographies (literary works); Autobiographies; Biographies; Autobiographies; Biographies; Autobiographies; Biographies